Polyaniline-Invertase-Gold Nanoparticles Modified Gold Electrode for Sucrose Detection - Fitriyana Fitriyana; Fredy Kurniawan (Indonesian Journal of Chemistry, 2015)
Sucrose sensor has been made by deposited the active materials on the surface of gold electrode. The active materials, i.e. polyaniline (PANI), invertase and gold nanoparticles, were deposited step by step. Aniline polymerization were conducted electrochemically at potential -500 to 1000 mV using voltammetry method with sweep rate 50 mV/s for 20 cycles in HCl solution pH 1.5. The modified electrode obtained was immersed in invertase 1 M phosphate buffer solution pH 6. The invertase trapping in polyaniline was performed using the same condition as aniline polymerization. Then, gold nanoparticles were deposited on the polyaniline-invertase modified gold electrode using Layer by Layer (LbL) technique. The polyaniline-invertase-gold nanoparticles modified gold electrode obtained was used to measure sucrose solution. Electrochemical signal of polyaniline (PANI)-invertase-gold nanoparticles modified gold electrode is increase with sucrose concentration. The sensitivity and detection limit of the electrode are 0.4657 µA mm-2 mM-1 and 9 µM, respectively. No electrochemical interference signals from fructose and glucose have been observed in the sucrose measurement.